UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MATERI PENYAJIAN DATA MELALUI MODEL DISCOVERY LEARNING PADA SISWA KELAS VII C SISWA SMP NEGERI 2 MUNTILAN - Tien Dwikoraningrum (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
One of the problems in learning mathematics is the weak ability of students to apply knowledge to solve problems in real life, especially in solving the problem of presenting Data, collecting data, and presenting data. To overcome this problem, a class action research (PTK) was conducted using Discovery Learning model. The purpose of this study was to improve the learning outcomes of VII C grade students of SMP Negeri 2 Muntilan school year 2018/2019 using the Discovery Learning Learning model. The research subjects were students totaling 32 people, the source of research data obtained from qualitative data in the form of data observation activities of teachers and students and quantitative data in the form of student learning outcomes test data. The results of the first cycle of research obtained by students who completed individually as many as 24 students with classical completeness of 75 %. While the results of the second cycle of research has increased with the number of students who completed individually as many as 28 students with a percentage of completeness of 87.5 %. Based on the results of the study, learning using the Discovery Learning Learning model can improve the learning outcomes of VII C grade students of SMP Negeri 2 Muntilan school year 2018/2019.